Dental Health and Pregnancy – An Overview - Balasubramaniam Anuradha1 , Narasimhan Manasa2 , Suresh Mitthra3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Pregnancy is a physiological state with significant changes in a woman’s body. Pregnant women are moreprone to gingival diseases due high levels of fluctuating pregnancy hormones.The aim of this article is tobring to light the changes in oral cavity during pregnancy, the consequences of not treating them and thecurrent recommendations for dental management of pregnant patients in different trimesters.